1998
DOI: 10.5271/sjweh.362
|View full text |Cite
|
Sign up to set email alerts
|

Year of birth and sperm count in 10 Danish occupational studies

Abstract: Objectives Several reports indicate a secular decline of human sperm counts. It is still not known if these findings are artifacts related to shortcomings in the data and applied methodologies. Even less is known about possible mechanisms, but it has been proposed that potential changes may be related to disruption of the hormonal regulation of testicular development in prenatal life. The objective of this study was to examine whether sperm count was related to year of birth. Methods An analysis was made of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 28 publications
2
29
0
1
Order By: Relevance
“…Some data have shown that sperm count rates have declined over the last 50 years with current reference ranges of approximately 15 million/mL (Swan, Elkin et al , 2000; Swan and Elkin, 1999; Swan, Elkin et al , 1997; Bonde, Kold et al , 1998; Rolland, Le Moal et al , 2103; Cooper, Noonan et al , 2010; Fisch, Goluboffe et al , 1996). However, other data are equivocal with regard to global semen quality parameters (Fisch 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Some data have shown that sperm count rates have declined over the last 50 years with current reference ranges of approximately 15 million/mL (Swan, Elkin et al , 2000; Swan and Elkin, 1999; Swan, Elkin et al , 1997; Bonde, Kold et al , 1998; Rolland, Le Moal et al , 2103; Cooper, Noonan et al , 2010; Fisch, Goluboffe et al , 1996). However, other data are equivocal with regard to global semen quality parameters (Fisch 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, evidence is emerging that semen quality is lower among younger cohorts. A meta-analysis of semen quality of normal Danish men suggested a birth cohort-related decline in semen quality [70], and the trend seems to continue as the younger cohorts born around 1980 had the lowest sperm counts of all cohorts examined (Fig. 2) [69].…”
Section: Male Factorsmentioning
confidence: 98%
“…Although controversial, gradual but steady declines in the number and quality of sperm [1][2][3] as well as levels of biologically available or free serum testosterone (T) [4,5] have been reported with advancing age. Agerelated differences in the human testis include reductions in volume or number of T-producing Leydig cells and changes in the morphology and number of germ-cell-supporting Sertoli cells, either of which may contribute to the age-related degeneration of germ cells during spermatogenesis [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%